2022
DOI: 10.4196/kjpp.2022.26.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA reduces pyroptosis in rats with coronary microembolization by inhibiting the TLR4/MyD88/NF-κB/NLRP3 pathway

Abstract: Pyroptosis is an inflammatory form of programmed cell death that is linked with invading intracellular pathogens. Cardiac pyroptosis has a significant role in coronary microembolization (CME), thus causing myocardial injury. Tanshinone IIA (Tan IIA) has powerful cardioprotective effects. Hence, this study aimed to identify the effect of Tan IIA on CME and its underlying mechanism. Forty Sprague–Dawley (SD) rats were randomly grouped into sham, CME, CME + low-dose Tan IIA, and CME + high-dose Tan IIA groups. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Pyroptosis was also involved in myocardial damage caused by CME. Inhibiting myocardial pyroptosis could improve myocardial damage caused by CME and improve cardiac function of rats [ 13 , 19 , 34 ]. In this study, we confirmed that CME induced cardiomyocyte pyroptosis by means of molecular biology.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis was also involved in myocardial damage caused by CME. Inhibiting myocardial pyroptosis could improve myocardial damage caused by CME and improve cardiac function of rats [ 13 , 19 , 34 ]. In this study, we confirmed that CME induced cardiomyocyte pyroptosis by means of molecular biology.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial pyroptosis was found to be involved in the development of CME; however, tanshinone IIA can delay this process. The underlying mechanism is that tanshinone IIA reduces cardiomyocyte pyroptosis by inhibiting the TLR4/MyD88/NF-κB/NLRP3 pathway ( Li et al, 2022 ). The mechanisms by which plant metabolites inhibit pyroptosis are listed in Table 1 .…”
Section: Treatment Of Hf With Tcm Formulations Inhibits Pyroptosismentioning
confidence: 99%